Consumer health information organising and mobile acquiring based on topic maps. (2016) - Zhang, Junsheng; Sun, Yunchuan; Li, Yingying; Wang, Huilin
It is difficult for consumers to find, understand and share health information due to the limitations of the current health information systems. Major problems include the missing of connections between multilingual medical terms and the gap between obscure medical terminologies used by experts and common vocabularies used by consumers. This paper utilises the topic maps model to organise consumer health information by linking professional medical terminologies in different languages and the corresponding common vocabularies. The proposed approach is applied into organising bilingual (Chinese and English) consumer health information resources in the diabetes domain. Topic maps tools designed by the Ontopia corporation are used to organise the consumer health information resources about diabetes mellitus. Experiment results show that topic maps of health information are suitable for bilingual health information organising and mobile information acquiring on mobile devices.